2005
DOI: 10.1111/j.1742-7843.2005.pto_96696601.x
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants in the Treatment of Neuropathic Pain

Abstract: Neuropathic pain is due to lesion or dysfunction of the peripheral or central nervous system. Tricyclic antidepressants and anticonvulsants have long been the mainstay of treatment of this type of pain. Tricyclic antidepressants may relieve neuropathic pain by their unique ability to inhibit presynaptic reuptake of the biogenic amines serotonin and noradrenaline, but other mechanisms such as N-methyl-D-aspartate receptor and ion channel blockade probably also play a role in their pain-relieving effect. The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
295
0
17

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 501 publications
(317 citation statements)
references
References 69 publications
5
295
0
17
Order By: Relevance
“…P2X4 receptors are relatively insensitive to broad-spectrum P2X antagonists, suramin and PPADS [3,14], and although a specific P2X4 antagonist has been reported [39], data regarding its effectiveness and specificity have not yet been published. Tri-cyclic antidepressant drugs such as paroxetine, fluoxetine, desipramine and amitriptyline have been prescribed for many years for the treatment of neuropathic pain [40] and were recently shown to inhibit P2X4 receptor function [15], a mechanism which may contribute to their analgesic properties. However, recent studies by Toulme et al [17] have shown that, with the exception of paroxetine which has some direct effects on P2X4 currents, these drugs act by disrupting lysosomal function and the trafficking of P2X4 receptors to the plasma membrane and are, therefore, not true P2X4 antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…P2X4 receptors are relatively insensitive to broad-spectrum P2X antagonists, suramin and PPADS [3,14], and although a specific P2X4 antagonist has been reported [39], data regarding its effectiveness and specificity have not yet been published. Tri-cyclic antidepressant drugs such as paroxetine, fluoxetine, desipramine and amitriptyline have been prescribed for many years for the treatment of neuropathic pain [40] and were recently shown to inhibit P2X4 receptor function [15], a mechanism which may contribute to their analgesic properties. However, recent studies by Toulme et al [17] have shown that, with the exception of paroxetine which has some direct effects on P2X4 currents, these drugs act by disrupting lysosomal function and the trafficking of P2X4 receptors to the plasma membrane and are, therefore, not true P2X4 antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…43 Additionally, the tricyclic antidepressant amitriptyline and the cannabinoid agonist WIN 55,212-2 were found to reverse VZV-induced mechanical allodynia, and both have been found effective in clinical trials for either PHN or other neuropathic conditions. 43,80,81 In summary, these preclinical investigations have revealed similarities between a rodent model of chronic pain induced by VZV infection and models of chronic pain from peripheral nerve injury, although more investigation is needed to reveal whether there are physiological changes specific to the VZV model.…”
Section: Preclinical Evaluationsmentioning
confidence: 99%
“…Anticonvulsants such as pregablin and gabapentin are often prescribed and are effective for patients with postherpetic neuralgia, fibromyalgia and diabetic peripheral neuropathy [5]. For over 40 years, antidepressants such as tricycles, selective serotonin reuptake inhibitors and serotonin norepinephrine reuptake inhibitors have been used for the treatment of neuropathic pain and show efficacy for some patients [6]. Steroids are generally used as an adjunct therapy with opioids and are beneficial to patients with metastatic bone pain, visceral pain and neuropathic pain [7].…”
Section: Therapeutics For Chronic Neuropathic Painmentioning
confidence: 99%